Evaluation Of Semen And Non-Return Rate Of Bulls In Artificial Insemination (AI) Center (Bangladesh Journal of Animal Science, 2012)
The experiment was conducted to evaluate the bull performance based on semen quality and 60 days non-return rate. Data were collected from 60 ejaculates and 525 services. Semen for insemination was used from bulls of different genetic groups (2 Holstein cross, 1 Sindhi cross, 1 Sahiwal cross and 1 Red Chittagong). Individual bull effect was found to be significant (P